The protective role of exogen melatonin on the prostate gland under experimental models of metabolic diseases - Gobbo, Marina Guimarães [UNESP]; Tamarindo, Guilherme Henrique; Taboga, Sebastião Roberto [UNESP]; Góes, Rejane Maira [UNESP] (My University, 2018)
The prostate is an accessory gland of the male apparatus which is regulated by sexual steroids from its development phase. Several studies have reported that metabolic syndromes may also influence the prostate's physiology. Studies from our research group as well as other studies from the literature revealed that diabetes and high lipid intake are unfavorable to the prostatic homeostasis and may raise histophysiological alterations that can lead to cancer. Prostate stromal remodeling, imbalance on the gland proliferation/apoptotic rate, testosterone/estrogen ratio and tissue antioxidant system impairment are important features observed under metabolic disturbances and are often associated with carcinogenesis. In the last decade, the therapeutic potential of melatonin has been investigated due to it exerting antioxidant properties and influencing cell dynamics. As well as prostate cells expressing MTR1 and MTR2 receptors, the gland responses to melatonin treatment may also be triggered by several pathways, including the androgen pathway, antioxidant enzymes modulation and, as recently reported by our research group, changes in mitochondrial physiology. We have published articles describing conditions where tissue damage was induced, such as long-term diabetes,when animals treated with low melatonin doses showed an effective restoration of their prostate homeostasis and functions and managed to recover cell proliferation. It is worth mentioning that melatonin also raised testosterone serum levels, which were impaired after long-term diabetes induction. Hyperglycemia is often associated to an increase in oxidative stress, which leads to damage and cell death. Melatonin supplementation, even at low doses, promoted the normalization of activities of antioxidant enzymes on the prostate, which can be associated with reduced apoptosis indexes. In addition, our experiments with human epithelial prostate cells with high proliferative potential proved that melatonin has antioxidant properties due to strongly reduced oxygen reactive species (ROS) generation associated to increased oxidative phosphorylation (OXPHOS). Although melatonin has been considered beneficial for the prostate gland under normal or diabetogenic situations, its effects on cell proliferation are still poorly understood. At pharmacological concentrations it may exert anti-clonogenic effects both under normal conditions and after a short period of pre-incubation of prostatic benign and cancerous cells in a hyperglycemic medium. On the other hand, with longer pre-incubation it may favor cell proliferation. Obesity is also considered a metabolic disorder and when associated with prostate aging had been reported to favor prostatic lesions. In this context, melatonin administration to middle-aged rats was able to recover prostatic morphology and strongly decrease amyloid bodies' deposition even after obesity exposure. These results were probably related to total glutathione S-transferase (GST) activity improvement. Interestingly, under pro-oxidant conditions, generated by docosahexaenoic acid incubation (omega-3 fatty acid), the indole not only reduced dramatically ROS generation and enhanced OXPHOS, but also restored cell capacity to survive stress situations independently of the sensitization of the membrane receptors. Furthermore, our studies also suggest melatonin supplementation as a benign prostate hyperplasia chemoprevention method due to the decreased cell proliferation it promotes, even in a hyperlipidemic medium. Our studies revealed that melatonin exerts a protective role on the prostate gland under several metabolic conditions in rodents, human benign prostatic hyperplasia models and cancer cells.
Keywords: Diabetes; Melatonin; Obesity; Oxidative stress; Prostate